Intravenous Palonosetron for Attenuation of Hypotensive Response and Bradycardia during Spinal Anaesthesia - Suvidha Sood, M.D.,; Yogesh Roy, MBBS,; Anupriya Saxena, MBBS, (International Journal of Innovative Research in Medical Science, 2021)
Aim: This study was conducted to evaluate the role of intravenous (IV) palonosetron during spinal anesthesia. Method: A total of 100 patients undergoing elective lower limb and lower abdominal surgeries were randomly divided into two groups. Group P was given 0.25mg palonosetron diluted in 10 ml normal saline slowly before spinal anesthesia. Group S was given 10 ml of normal saline slowly before spinal anesthesia. Heart rate (HR) , systolic blood pressure (SBP) , diastolic blood pressure (DBP) , mean arterial pressure (MAP), oxygen saturation (SpO2) were monitored at an interval of 2 minutes for the initial 20 minutes, then at an interval of every 5 minutes till the end of the surgery. Time to reach the maximum sensory level and its regression two levels below and then till S1 was noted. The incidence of nausea, vomiting, shivering, use of intravenous mephenteramine, level of motor block and its regression were also recorded. Results: Decreases in HR were more observed in Group S and the differences were statistically significant at 25 min [p=0.048] and 30 min [p=0.047]. The decrease in MAP were observed more in Group S and statistically significant difference noted at 20 min [ p = 0.026], 25 min [ p = 0.046] and at 30 min [ p = 0.047]. The use of intravenous mephentermine [p = 0.009] and development of nausea [p = 0.049] were significantly more common in Group S, Sensory block regression was faster in group P. [p=0.054]. Conclusion: Premedication with 0.25mg IV palonosetron before spinal anesthesia reduces hypotension, bradycardia.